Core topics in endocrinology in anaesthesia and critical care - Cooper, Mark S.; Hall, George M.; Hunter, Jennifer M. (Cambridge University Press, 2010)
Core Topics in Endocrinology in Anesthesia and Critical Care provides a comprehensive, practical overview of the perioperative management of patients with endocrine disorders, giving clear diagnostic advice and management guidelines. This book considers the management of patients with endocrine disorders of the pituitary, thyroid, parathyroid and adrenal glands, including rarer disorders such as MEN syndrome. It then considers all aspects of the perioperative management of diabetic patients, including paediatric, obstetric and ambulatory patients. Finally it discusses endocrine disorders in the critically ill patient, covering such issues as the topical conundrum of glucose control and the management of diabetic metabolic acidosis, thyroid storm and myxoedema coma. Every chapter reviews the relevant anatomy and pathophysiology and the latest developments in defining the genetic causes are also considered where appropriate. Core Topics in Endocrinology in Anesthesia and Critical Care is an invaluable tool for all anaesthetists and intensivists in their daily clinical practice.